Synthesis and properties of 5-methyl-4-(4-methylphenyl)-1,2,4-Triazole-3-thiol derivatives - Plyska, А.; Gotsulia, A. S.; Гоцуля, Андрій Сергійович (X. : НФаУ, 2023)
The aim of the work was to conduct a set of studies aimed at identifying compounds with a pharmacological profile in a number of 5-methyl-4-(4- methylphenyl)-1,2,4-triazole-3-thiol derivatives.
Keywords: тези доповідей